"Functional upcycling" of polymer waste towards the design of new materials - Guselnikova, Olga; Semyonov, Oleg; Sviridova, Elizaveta; Gulyaev, Roman; Gorbunova, Alina; Kogolev, Dmitry; Trelin, Andrii; Yamauchi, Yusuke; Boukherroub, Rabah; Postnikov, Pavel (Chemical Society reviews, 2023)
Diversification of polymer waste recycling is one of the solutions to improve the current environmental scenario. Upcycling is a promising strategy for converting polymer waste into molecular intermediates and high-value products. Although the catalytic transformations into small molecules have been actively discussed, the methods and characteristics of upcycling into new materials have not yet been addressed. Recently, the functionalisation of polymer wastes (polyethylene terephthalate bottles, polypropylene surgical masks, rubber tires, ) and their conversion into new materials with enhanced functionality have been proposed as an appealing alternative for dealing with polymer waste recycling/treatment. In this review, the term 'functional upcycling' is introduced to designate any method of post-polymerisation modification or surface functionalisation without considerable polymer chain destruction to produce a new upcycled material with added value. This review explores the functional upcycling strategy with detailed consideration of the most common polymers, , polystyrene, poly(methyl methacrylate), polyethylene, polypropylene, polyurethane, polyethylene terephthalate, polyvinyl chloride, polycarbonate, and rubber. We discuss the composition of plastic waste, reactivity, available physical/chemical agents for modification, and the interconnection between their properties and application. To date, upcycled materials have been successfully applied as adsorbents (including CO ), catalysts, electrode materials for energy storage and sensing, demonstrating a high added value. Importantly, the reviewed reports indicated that the specific performance of upcycled materials is generally comparable or higher than that of similar materials prepared from virgin polymer feedstock. All these advantages promote functional upcycling as a promising diversification approach against the common postprocessing methods employed for polymer waste. Finally, to identify the limitations and suggest future scope of research for each polymer, we comparatively analysed the aspects of functional upcycling with those of chemical and mechanical recycling, considering the energy and resource costs, toxicity of the used chemicals, environmental footprint, and the value added to the product.